2014
DOI: 10.12968/bjcn.2014.19.11.544
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory prescribing at the end of life in Lothian care homes

Abstract: Common symptoms at the end of life include pain, breathlessness, anxiety, respiratory secretions and nausea. National end-of-life care strategies advocate anticipatory prescribing for timely management of these symptoms to enhance patient care by preventing unnecessary distress. This study investigated the extent to which residents in eight Lothian care homes had anticipatory medications prescribed prior to death. Data were collected as part of a service development project to improve palliative care in nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…50 Three retrospective studies in UK nursing home settings reported anticipatory prescribing rates varying from 37%, 43 28%–62%, 47 to 13–100%. 38 Although the data are limited by inadequate definitions of anticipatory prescribing, 43,47 patients at home or in care homes appear less likely to be prescribed drugs than those in nursing homes. 38,42,43,47 Surveys of community healthcare professionals suggest that anticipatory prescribing is widespread in the United Kingdom.…”
Section: What Is Current Practice?mentioning
confidence: 99%
See 3 more Smart Citations
“…50 Three retrospective studies in UK nursing home settings reported anticipatory prescribing rates varying from 37%, 43 28%–62%, 47 to 13–100%. 38 Although the data are limited by inadequate definitions of anticipatory prescribing, 43,47 patients at home or in care homes appear less likely to be prescribed drugs than those in nursing homes. 38,42,43,47 Surveys of community healthcare professionals suggest that anticipatory prescribing is widespread in the United Kingdom.…”
Section: What Is Current Practice?mentioning
confidence: 99%
“…Few studies investigated the frequency of anticipatory prescribing in the community: these were primarily limited to the United Kingdom, and patient samples do not accurately represent the general population. 38,40,42,43,47,50 Reported figures varied greatly across studies which may relate to differences in study design, context, and denominators used. 38,40,42,43,47,50 A study of 12 GP practices in one UK county reported that anticipatory prescribing occurred in 16% of all predictable deaths in the community (home or care home).…”
Section: What Is Current Practice?mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, that study GP (McClelland et al, 2008:96). In some care homes these relationships may be inadequate due to high staff turnover (Tilden et al, 2012, Finucane et al, 2014, or care home staff having limited knowledge of palliative care drugs and how to control symptoms (Watson et al, 2006). However, findings from the study reported here show that communication and trust between GPs and care home nurses was facilitated by a move to a single GP practice.…”
Section: Discussionmentioning
confidence: 66%